Real-Time Server Room Temperature and Visual Surveillance Monitoring Using ESP32-CAM Integrated with DHT22 Sensor: Sistem Monitoring Suhu dan Keamanan Ruang Server Secara Real-Time dengan ESP32-CAM dan Sensor DHT22 - Melia Sari (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2026)
Server rooms are critical information technology infrastructures where uncontrolled temperature fluctuations can cause permanent hardware damage. The ASHRAE TC 9.9 standard recommends server room temperatures within the range of 18°C–27°C; however, many mid-scale institutions lack integrated real-time temperature and visual monitoring systems. This study designs and implements an ESP32-CAM-based server room monitoring system integrating a DHT22 temperature sensor with a real-time web interface and a threshold-based alarm mechanism. The system was developed using an experimental approach, encompassing sensor accuracy testing, alarm response evaluation, data transmission latency measurement, and operational reliability testing. Test results show that the DHT22 sensor has an average temperature measurement error of 1.18% over the 20°C–35°C range, with an RMSE of 0.177°C. The system detects critical temperature threshold breaches (35°C) with an average latency of 1.9 seconds and automatically activates a local buzzer alarm. Data transmission latency on a local LAN reaches 110–160 ms with video streaming at 15–20 FPS at 640×480 pixel resolution. System uptime reached 99.7% during 24-hour operational testing, including power outage scenarios supported by a mini UPS module. The developed system proves capable of providing early warning against critical thermal conditions at a low-cost component making it a comprehensive low-cost solution suitable as an alternative Building Management System (BMS) for budget-constrained institutions.